Hubungan Antara Platelet-To-Lymphocyte Ratio dan Kadar Troponin I Pada Pasien Infark Miokard Akut Elevasi Segmen ST: Correlation Of Platelet-To-Lymphocyte Ratio And Troponin I Levels In Patients With St-Elevation Myocardial Infarction - Tamariska Evelyn; Pipin Ardhianto; Dwi Retnoningrum; Mochamad Ali Sobirin (RSUP Dr. Kariadi, 2022)
INTRODUCTION: Platelet and lymphocyte are significant in acute myocardial infarction (AMI) pathogenesis. Platelet-lymphocyte ratio (PLR) is a systemic biomarker which indicates thrombosis and inflammation. The diagnosis of AMI can be made by detecting elevated blood troponin I levels. The correlation between PLR and troponin I levels in ST-segment elevation myocardial infarction (STEMI) patients has not been widely known. AIM : The objective of this study is to determine the correlation between PLR and troponin I levels in STEMI patients. METHODS : This study was a cross-sectional study which data were obtained from the medical records of patients with STEMI admitted to Dr. Kariadi General Hospital Semarang from 2019 to 2020. Serum Troponin I levels were measured with Enzyme-Linked Fluorescent Assay (ELFA) method in less than 24 hours from symptoms onset. Complete blood counts were performed immediately on hospital admission. Correlations between variables were obtained using Spearman's test. RESULTS : A total of 28 STEMI patients were included, 82.1% were male, mean age was 55.81 ± 2.13 years old. Mean symptoms onset was 7.52 ± 0.81 hours prior to admission. Mean PLR and troponin I levels were 233.32 ± 25.54 and 14.44 ± 3.16 μg/l, respectively. A moderately significant correlation was detected between troponin I levels and PLR in STEMI patients (r=0.333; p=0.042). Symptoms onset in STEMI patients had significant correlation to troponin I levels (r=0.596; p=0.001). CONCLUSION : A moderate positive correlation between PLR and troponin I levels is observed within 24 hours from symptoms onset in STEMI patients. KEYWORDS: Platelet-to-lymphocyte ratio; ST-segment elevation myocardial infarction; troponin I